Legal Analysis of The Role of The Transportation Department in Supervising and Taking Action on Overloading Vehicles in Karanganyar Regency - Denisa Yunita Putri; Arief Budiono (Proceeding International Conference Restructuring and Transforming Law, 2026)
Introduction: Overloaded freight vehicles constitute a serious issue in road transportation systems as they contribute to traffic accidents and accelerate road infrastructure damage.Methods: This study aims to analyze the effectiveness of supervision and enforcement of overloaded freight vehicles by the Transportation Agency of Karanganyar Regency and to identify the obstacles encountered in its implementation. This research employs an empirical juridical method with statutory and field approaches through in-depth interviews and document studies.Novelty: This research offers a novel contribution by integrating a legal-institutional analysis with empirical findings on the implementation of supervision and enforcement mechanisms, particularly highlighting the limitations of administrative sanctions and intergovernmental authority fragmentation in addressing overloading violations.R&D: The findings indicate that supervision and enforcement have been carried out through preventive and repressive measures, such as vehicle inspection (VI), weighing at weighbridges, joint operations, ticketing, and load reduction. However, their effectiveness remains suboptimal as violations persist and sanctions are predominantly administrative in nature.Conclusion: The main obstacles include limited human resources, inadequate infrastructure and authority, economic pressure from freight companies, and structural constraints related to the division of authority between central and regional governments, which restrict the flexibility of supervision.